Formulation And Evaluation Of Pharmaceutical Emulgel With Indomethacin And Azadirachta Indica For Enhanced Analgesic And Anti-Inflammatory Effects - Prajapati, Anil; Gupta, M.K.; Prajapati, Ashish; Kumar, Suraj; Kumar, Suraj; Gond, Akshay (Journal of Neonatal Surgery, 2025)
Topical delivery systems such as emulgels offer a promising approach for the treatment of localized inflammation and pain by enhancing drug permeation and minimizing systemic side effects. Indomethacin, a potent NSAID, has limited water solubility and gastrointestinal side effects when administered orally. Azadirachta indica (Nimbidin) is a natural anti-inflammatory and antimicrobial agent known for its therapeutic potential. This study aimed to formulate and evaluate an emulgel incorporating Indomethacin and Azadirachta indica for enhanced analgesic and anti-inflammatory activity. Nimbidin was extracted from neem seeds using cold press and Soxhlet extraction methods. Emulgels were prepared using Carbopol 934 as a gelling agent and Span 80/Tween 80 as emulsifiers. The formulations were evaluated for physical appearance, pH, viscosity, spreadability, drug content, in vitro drug release, antimicrobial activity, skin irritation, and stability under accelerated conditions. The optimized formulation (F2) demonstrated desirable pH (5.9), viscosity (52,000 cps), and excellent spreadability. Drug content was within acceptable limits (Indomethacin: 98.4%, Nimbidin: 97.2%). In vitro release studies showed sustained drug release (94.1% over 8 hours). Antimicrobial activity and skin safety were confirmed. Stability studies indicated good retention of physical and chemical properties. The developed emulgel combining Indomethacin and Azadirachta indica exhibited enhanced therapeutic efficacy, favorable stability, and excellent topical tolerability, indicating its potential as an effective treatment for inflammatory and painful skin conditions.